ANALISIS PENYEBAB PENDING KLAIM BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN PASIEN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH WANGAYA - Dartini, Made Ayu; Wasita, Rai Riska Resty; Manik Nugraha, I Gusti Ngurah (Politeknik Kesehatan Kemenkes Malang, 2024)
One of the hospital's problems in implementing Social Health Insurance Administration Body (BPJS Kesehatan) claims is pending claims. Based on data on returning BPJS claims for inpatients in May-July 2022, 220 (11.3%) claim files were returned out of a total of 1,948 files submitted. There were 120 (54.5%) diagnosis code discrepancies, 32 (14.5%) action code discrepancies, 44 (20%) hospitalization indication discrepancies, and 17 (7.7%) hospitalization episode discrepancies. This study aims to describe the occurrence of claims discrepancies that cause pending claims for BPJS Kesehatan inpatients at the Wangaya Regional General Hospital, Denpasar City. The design of this research is descriptive qualitative. Data collection methods used are interviews, observation, checklists, and documentation. There were five research informants. Data analysis using triangulation analysis. The research results obtained showed that the discrepancy in the diagnosis code occurred due to incomplete medical records and unclear doctor writing. The action code discrepancy occurred because of incomplete operation report files and differences in language between doctors and ICD-9-CM. Discrepancies in the indications for hospitalization occur due to the non-fulfillment of hospitalization requirements. The discrepancy of hospitalization episodes occurred because of the inaccuracy of determining the episode by the officer. It is hoped that the hospital can evaluate the implementation of claims so that pending claims do not occur.